Shale : subsurface science and engineering - Dewers, Thomas A. 1961-; Heath, Jason (Geologist); Sánchez, Marcelo (Geotechnical engineer) (John Wiley & Sons, Inc. ; American Geophysical Union, 2020)
Advances in theories, methods and applications for shale resource use Shale is the dominant rock in the sedimentary record. It is also the subject of increased interest because of the growing contribution of shale oil and gas to energy supplies, as well as the potential use of shale formations for carbon dioxide sequestration and nuclear waste storage. Shale: Subsurface Science and Engineering brings together geoscience and engineering to present the latest models, methods and applications for understanding and exploiting shale formations. Volume highlights include: -Review of current knowledge on shale geology -Latest shale engineering methods such as horizontal drilling -Reservoir management practices for optimized oil and gas field development -Examples of economically and environmentally viable methods of hydrocarbon extraction from shale -Discussion of issues relating to hydraulic fracking, carbon sequestration, and nuclear waste storage'
Keywords: Shale.; Shale gas.; Shale oils.; Carbon sequestration.; elektronické knihy; electronic books